Incomplete typescript copy of an essay or speech on education in Northern Ireland following partition - Duggan, Éamonn, 1874-1936
The document relates to the possible impact of Northern Irish legislation on education within the six counties, notably the increased secularisation of Northern Irish education, and the Catholic Church's possible opposition to any changes to the system. The authorship of the document is unclear.
Pages are numbered 2 to 12; page 2 is a photocopy of the typescript original.
Keywords: Education -- Northern Ireland